Genome of Hippophae rhamnoides provides insights into a conserved molecular mechanism in actinorhizal and rhizobial symbioses. Issue 1 (3rd March 2022) - Wu, Zefeng; Chen, Hongyun; Pan, Ya; Feng, Huan; Fang, Dongming; Yang, Jun; Wang, Yayu; Yang, Jun; Sahu, Sunil Kumar; Liu, Jianling; Xing, Yu'e; Wang, Xiaolin; et al.
Summary: Sea buckthorn ( Hippophae rhamnoides ), a horticulturally multipurpose species in the family Elaeagnaceae, can build associations with Frankia actinomycetes to enable symbiotic nitrogen‐fixing. Currently, no high‐quality reference genome is available for an actinorhizal plant, which greatly hinders the study of actinorhizal symbiotic nodulation. Here, by combining short‐read, long‐read and Hi‐C sequencing technologies, we generated a chromosome‐level reference genome of H. rhamnoides (scaffold N50: 65 Mb, and genome size: 730 Mb) and predicted 30 812 protein‐coding genes mainly on 12 pseudochromosomes. Hippophae rhamnoides was found to share a high proportion of symbiotic nodulation genes with Medicago truncatula, implying a shared molecular mechanism between actinorhizal and rhizobial symbioses. Phylogenetic analysis clustered the three paralogous NODULE INCEPTION (NIN) genes of H. rhamnoides with those of other nodulating species, forming the NIN group that most likely evolved from the ancestral NLP group. The genome of H. rhamnoides will help us to decipher the underlying genetic programming of actinorhizal symbiosis, and our high‐quality genome and transcriptomic resources will make H. rhamnoides a new excellent model plant for actinorhizal symbiosis research.